1997
DOI: 10.1128/jvi.71.1.738-740.1997
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of bovine leukemia virus with target cells monitored by R18 fluorescence and PCR assays

Abstract: PCR and R18 fluorescence dequenching assays have been combined to monitor the kinetics of fusion of bovine leukemia virus with target cells (CC81, OVK, or Raji). Antibodies raised against gp51 allow us to demonstrate that not only the hydrophobic N-terminal domain of the transmembrane glycoprotein gp30 but also specific domains of gp51 (amino acids 39 to 103) are involved in bovine leukemia virus-cell fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…The results of antibody detection by SIIA revealed that colostrum from infected cattle inhibited syncytium induction caused by BLV infection. Syncytium formation results from cell-to-cell fusion caused by BLV gp51, an outer membrane glycoprotein [12, 13]. Previous studies showed the complement-dependent cytotoxicity of anti-gp51 antibody [14, 15], and previous studies hypothesized that the protective effect of BLV infection mediated by immunoglobulin (Ig) G would be conferred by anti-glycoprotein antibodies [16].…”
Section: Discussionmentioning
confidence: 99%
“…The results of antibody detection by SIIA revealed that colostrum from infected cattle inhibited syncytium induction caused by BLV infection. Syncytium formation results from cell-to-cell fusion caused by BLV gp51, an outer membrane glycoprotein [12, 13]. Previous studies showed the complement-dependent cytotoxicity of anti-gp51 antibody [14, 15], and previous studies hypothesized that the protective effect of BLV infection mediated by immunoglobulin (Ig) G would be conferred by anti-glycoprotein antibodies [16].…”
Section: Discussionmentioning
confidence: 99%
“…The first technique is testing the effects of agents, such as bafilomycin, that inhibit endosomal acidification. In some studies of this type, fusion has been measured directly by assessing the transfer of fluorescent probes from the virus to the target cell (Earp et al 2003;Irurzun et al 1997;Zarkik et al 1997). In others, fusion has been inferred by monitoring postfusion events, such as the synthesis of viral DNA (Mothes et al 2000).…”
Section: Low Ph Activationmentioning
confidence: 99%
“…Моноклональные антитела против эпитопа H способны полностью блокировать слияние клеток в культуре. Антитела против эпитопов F и G менее эффективно снижают способность вируса к формированию синцития [27]. Помимо гуморального иммунитета, поверхностная субъединица также стимулирует Т-клеточный ответ, что продемонстрировано наличием хелперов CD4+ и эпитопов для цитотоксических CD8+ Т-лимфоцитов (CTL).…”
Section: организация генома вируса Blvunclassified